METHODOLOGY FOR TEACHING OF PHRASEOLOGICAL UNITS WITH A COLOR NAMING COMPONENT TO FOREIGNERS - Chernova , Natalia; Antonova , Natalia; Kharitonova, Olga (Revista Inclusiones, 2020)
The article makes a strong case for the development of didactic principles of teaching of Russian phraseology with the components of color designation. It describes color as a component of culture of language. In the paper a system of exercises for the formation of competencies in the field of phraseology with the components of color designations is presented.